Attractiveness and Sexual Competitiveness of Anastrepha obliqua Males (Diptera: Tephritidae) Fed on a Diet Enriched With Providencia rettgeri - Roque-Romero, Linnet; Hernández, Emilio; Aceituno-Medina, Marysol; Ventura, Carmen; Toledo, Jorge; Malo, Edi A. (Frontiers in Microbiology, 2020)
The West Indian fruit fly, Anastrepha obliqua (Macquart), is the second most important tephritid fruit fly in Mexico that infests mango, plum and guava fruits. To control it, the Mexican government implemented the use of the Sterile Insect Technique (SIT). The SIT involves the mass production and sterilization of flies. However, A. obliqua laboratory males used in SIT are less selected by the wild females during competitiveness tests. The objective of this work was to compare the effects of males feeding on Mubarqui® fruit fly food (Mb®) enriched with Providencia rettgeri against males feeding on Mb® food alone, assessing the males mating competitiveness, the capture of females using traps baited with males fed with the enriched food and sex pheromone components. The results indicated that the males fed with the food enriched with P. rettgeri had an increased mating competitiveness and captured more females during the field cage tests. Seven volatile compounds were identified during the calling of A. obliqua males ((Z)-3-nonenol, nonadienol, sesquiterpene, (E,Z)-α-farnesene, β-farnesene (E,E)-α-farnesene and farnesene isomer). These results suggest consideration of the use of bacteria in the mass rearing technique of A. obliqua adults to improve the sexual competitiveness of males from the laboratory compared to wild males.